Assurance of Halal Beef Products Using a Traceability System in Enterprise Resource Planning Applications - Kusnadi, Adhi; Arkeman, Yandra; Syamsu, Khaswar; Hartono Wijaya, Sony (IOP conference series. Earth and environmental science, 2024)
This research addresses the critical issue of maintaining consumer trust in the halal products within the Indonesian context, specifically focusing on beef products. Recognizing the vulnerability of halal products and counterfeit certificates, the study proposes an innovative solution through the implementation of an Enterprise Resource Planning (ERP) application. This application is designed to trace and monitor the halal beef supply chain, aligning with the certification standards set by the Indonesian Ulema Council (MUI). The choice of beef as the subject of this study stems from its high susceptibility to counterfeiting and the complexity of its supply chain. The research utilizes an ERP system for its comprehensive enterprise-level management capabilities, including aspects of purchasing, inventory, and manufacturing. This technology integration aims to address the challenges in tracing halal beef products from their origin to the consumer (upstream to downstream), ensuring compliance with halal requirements and optimizing the supply chain. Methodologically, the development of this traceability system adheres to the System Development Life Cycle (SDLC), employing a modified waterfall model. The system’s efficacy is evaluated through Blackbox testing, demonstrating its capability to effectively track the journey of halal beef products. It ensures validation at each stage of the supply chain in accordance with MUI’s halal certification criteria and provides rapid tracking capabilities in emergency situations. In conclusion, this study presents a significant technological innovation in the field of halal product assurance. It offers an integrated solution that combines information technology and management principles to uphold the integrity of halal products, thereby safeguarding consumer trust and supporting the reputation of conscientious manufacturers in Indonesia.